2019
DOI: 10.1016/j.ijms.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Selective C H bond activation of ethane by free gold clusters

Abstract: The activation and potential dissociation of ethane mediated by small cationic gold clusters Au x + (x = 2-4) has been explored by infrared multiphoton dissociation (IR-MPD) spectroscopy and density functional theory (DFT) calculations. The calculations show that the interaction between the gold clusters and ethane is mainly governed by the mixing of the ethane CH 3 bond-forming orbitals-(CH 3) with gold d-orbitals. While the CC single bond appears to be unaffected, this mixing leads to the selective activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
9
0
1
Order By: Relevance
“…The C81–C82 distance, however, is 1.62(2) Å, much longer than the above-mentioned C–C triple bonds or even a typical C–C single bond (ca. 1.54 Å) . Therefore, there is likely no bonding interaction between the two C atoms in the USc 2 C 2 moiety, a rare observation for an endohedral carbide cluster.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The C81–C82 distance, however, is 1.62(2) Å, much longer than the above-mentioned C–C triple bonds or even a typical C–C single bond (ca. 1.54 Å) . Therefore, there is likely no bonding interaction between the two C atoms in the USc 2 C 2 moiety, a rare observation for an endohedral carbide cluster.…”
Section: Resultsmentioning
confidence: 98%
“…1.54 Å). 25 Therefore, there is likely no bonding interaction between the two C atoms in the USc 2 C 2 moiety, a rare observation for an endohedral carbide cluster.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous spectroscopic studies on metal and metal oxide complexes demonstrated that the preparation of cluster complexes under the high-pressure multicollision conditions prevailing in the flow tube reactor is especially suitable for studying the initial steps of a chemical reaction, i.e., the fundamental interaction of the molecules with the clusters and the initial bond activation and bond breaking processes (see e.g. refs ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher binding energy of the C 2 H 6 is due to the mixing of the occupied π − (CH 3 ) orbitals with the Au( i ) orbitals resulting in an electron charge donation from C 2 H 6 to Au( i ) and a partial de-occupation of the π − (CH 3 ). 31 The partial de-occupation is reflected in the lowest unoccupied molecular orbital (LUMO) that is formed by the interaction of the occupied π − (CH 3 ) of ethane and unoccupied s-orbitals of Au( i ). The C 2 H 4 stabilizes the π mode adsorption and strengthens the Au–C bond by readily balancing between donation and back-donation of electrons which strongly influence the molecular adsorption.…”
Section: Resultsmentioning
confidence: 99%